Modelo distribuído aplicado à análise de evaporadores do tipo tubo aletado - Pimenta, Paulo Henrique Neves [UNESP] (2015)
This work presents a numerical model to simulate the steady and transient flow and heat transfer between the refrigerant fluid and outside air along tube-fin evaporators commonly used in 'no-frost' household refrigerators. The refrigerant flow inside the tube is taken as one- dimensional and divided in a two-phase flow region and a superheated vapor flow region. The refrigerant pressure drop and the moisture condensation on the airflow crossing the outside of the tubes are taken into account. The homogeneous flow model is employed for the two-phase flow region. The fundamental equations of mass conservation, momentum and energy conservation governing the refrigerant flow are solved in order to evaluate the velocity, pressure and specific enthalpy of the refrigerant fluid. The energy and mass (humidity) conservation equations for the air flow are solved in order to evaluate the temperature and absolute humidity of the air crossing the evaporator, respectively. The energy conservation equation for the evaporator tube wall is also solved to obtain the wall temperature distribution. Furthermore, the model needs closer constitutive equations to calculate the friction coefficients, the refrigerant and air heat transfer coefficients, the water mass transfer coefficient and the refrigerant, air and water thermo-physical properties. The governing equations are integrated numerically using Euler's method and the resulting algebraic system of equations is solved by Newton-Raphson's method. The model could be used to: (a) determine evaporator performance parameters, such as: refrigeration load; outlet refrigerant and air temperatures; among others, since the evaporator operating conditions and dimensions are known. In this case a direct problem is solved from a set of inlet conditions for the refrigerant and also for the air; (b) determine the refrigerant mass flow rate along evaporator tubes, once its ...